Transactional and Transformational Leadership Styles on the Effectiveness of Work From Home and Work Productivity - Daniel Joel Immanuel Kairupan (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
During the work-from-home (WFH) period, employees faced a new situation. Employees are required to adapt to the new situation. Changes in situations and demands and problems from working in the office to working at home, especially during a pandemic, certainly require leaders to show proper leadership behavior. Leaders need to find ways to increase employee work productivity, especially when the WFH work system begins to be implemented. This research was conducted to examine the impact of transactional and transformational leadership on productivity and performance effectiveness during the implementation of remote systems or work-from-home. Researchers chose transactional and transformational leadership because in writing this scientific paper, researchers found many previous articles that raised transactional and transformational leadership types as their research topic, but rarely examined the extent to which transactional and transformational leadership styles affect WFH effectiveness and employee work productivity. This study used a survey method with samples of employees who used remote systems during the Covid-19 pandemic era. Data collection was carried out using an online questionnaire using Google Forms. The statistical tool used to process the data is SPSS Statistics 22. Researchers also hope that the results of this research can become new insights for businesspeople in dealing with changes in the work-from-home system or remote system.